Effects of Xylanase and monensin sodium on growth in broilers - Boyer, Matthew G.; Delfelder, C.J.; Beyer, R. Scott; Stark, Charles R.; Evans, C.E.; Yoder, Ashton D.; Jones, Cassandra K. (My University, 2017)
Antibiotics are widely used in animal feeds to increase growth performance. There is increasing concern among consumers over the use of antibiotics due to the development of antibiotic resistance in humans. In the United States, it is estimated that 20% of cases involving antibiotic resistance are a result from animal agriculture. This study was performed to test exogenous xylanase as a potential replacement for antibiotics and its effects on growth performance compared to monensin sodium. 216 1-day-old Cobb broiler chicks were given 1 of 6 diets based with corn or wheat. Some of these diets were supplemented with 0.10 g/kg monensin sodium (Coban 90; Elanco Animal Health, Greenfield, IN) or 16,000 betaxlylanse units/kg beta 1-4, endo-xylanase enzyme (Econase XT; AB Vista, Marlborough, UK). The treatments were as follows: 1) Corn-based without xylanase or monensin sodium, 2) Wheat-based without xylanase or monensin sodium, 3) Corn-based with xylanase but no monensin sodium, 4) Wheat-based with xylanase but no monensin sodium, 5) Corn-based with monensin sodium but no xylanase, 6) Wheat-based with monensin sodium but no xylanase. Birds were randomly distributed into battery cages for 21 days fed ad libitum. A total of 36 cages were used with 6 birds in each cage. Cage weights and feed intake were recorded weekly to determine body weight, total feed intake, and feed conversion rate (FCR). This data was compiled and analyzed using the GLIMMIX procedure of SAS with cages as the experimental unit and treatments as the fixed effect. Treatments affected (P<0.01) final body weight, feed intake, and FCR. The corn-based control diet (P<0.05) had an improved effect on the FCR when compared to the wheat-based control diet. Corn-based diets altered with xylanase or monensin sodium did not improve (P>0.05) FCR beyond that of the corn-based control diet. The wheat-based diet with monensin sodium did not improve (P>0.05) FCR beyond that of the wheat-based control, but the wheat diet with xylanase did improve (P<0.05) FCR to levels similar to the corn-based diets. In conclusion, the data suggests that xylanase improves digestibility and thus, FCR, in wheat-based diets to levels found in corn-based diets while in a battery cage setting. Antibiotics seemed to have a limited effect on growth performance due to the structure of the cages.
Keywords: Spring 2017